STUDI EVALUASI KETERLAMBATAN PROYEK PENINGKATAN JALAN HOTMIX LALA–KARANG JAYAe: (Study of Delay Evaluation of the Hotmix Lala – Karang Jaya Road Improvement Project) - Assagaf, Ye Fahmi; Assagaf, Sjaid S. Fais (Uniqbu Journal of Exact Sciences, 2022)
The project delay occurred in the implementation of the Lala - Karang Jaya hotmix road improvement work in the 2021 fiscal year. Therefore, this study was conducted to determine what factors affect the delay in the implementation of the Lala - Karang Jaya hotmix road improvement project and find the most important factor. dominant influence it, so that it can determine the right strategy to overcome it. The data analysis methodology used is multiple linear regression analysis of the answers to the questionnaire distributed to 30 respondents from contractors, owners and consultants involved in the work of the Lala - Karang Jaya hotmix road improvement project in 2021. Based on the results of the study, the F test was obtained that simultaneously all factors have a simultaneous effect on the delay in the implementation of the Lala - Karang Jaya hotmix road improvement project with a calculated F value = 3.302 > from F table = 2.620. However, based on the partial t test, the factors that significantly influence the delay in the implementation of the Lala - Karang Jaya hotmix road improvement project are the Equipment factor (X3), with t count = 2.795 > t table = 1.7108. The most dominant factor is the Equipment factor (X3) with a coefficient of 0.291. Therefore, the strategy used to overcome this is to strive for the contractor to test the quality and quantity of the material used in accordance with technical specifications and also pay more attention to the quality of the equipment used.